The Effect of Management Change, Financial Distress, and Earnings Management on Audit Report Lag with the Number of Commissioners as a Moderating Variable - Nuladani, Galuh Setri; Saputra, Dian (GoAcademica Research & Publishing, 2024)
Audit report lag or the timeline for completing the audit needs special attention for companies because it significantly contributes to preserving the relevance financial statements. The aim of this study is to examine and provide empirical evidence regarding influence the management of change, financial distress and earnings management on audit report lag with the number of commissioners as a moderating variable. This research was carried out at the mining companies listed on the Indonesia Stock Exchange in 2020-2022. Types of data used is secondary data is provided in the form of audited financial reports. Method of data analysis uses Structural Equation Modeling-Partial Least Square (SEM-PLS). The findings indicated that management change and earnings management had no effect on audit report lag, while financial distress had a significant effect on audit report lag and was strengthened by the number of boards of commissioners as a moderating variable. However, the number of boards of commissioners is not supported to be a moderating variable that strengthens the effect of management changes and earnings management.